Effect of Interfacial Roughness on Mechanical and Thermo-Acoustic Behavior of Corn Husk Fiber. Issue 1 (31st December 2023) - Singh, Priyanka P.; Nath, G.
ABSTRACT: The designing of acoustic material with high efficiency absorption is cutting edge research for acoustician as well as architectures' in the acoustic industries attracts the material scientist due to its numerous significant characteristic properties. Nondestructive technique such as ultrasonic processing is employed for surface modification of corn husk which changes the interfacial as well as skeletal arrangement in interlocking of fibers with polymer chain. Tensile strength of single corn husk fiber before and after surface treatment was observed to be increasing from 332.57 MPa to 345.16 MPa, which confirms the strong fibrillation due to surface treatment. Further the hardness of the fabricated corn husk composite was found to be 23HV as observed in three different places. Thermal conductivity of the samples increases with temperature supporting the validation of the sample for acoustic application. The high sound absorption performance of the composite classified the material as Class-A type with 0.94 absorption coefficient supported by the different characterization and surface analysis of the composite.